Wolf Mask - Museum of Fine Arts (Scholars Resource, Inc., 1850)
The wooden mask appears to be that of an animal such as a wolf. Behind the mask, circular pieces hold the face and the hanging decorative elements from the head of the animal. The head is painted black and white.